2022
DOI: 10.1177/03635465221108187
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation in Posterior Tibial Slope by Sex, Age, and Race: A Cadaveric Study Utilizing 3-Dimensional Computerized Tomography

Abstract: Background: Posterior tibial slope (PTS) has recently gained increased attention for its possible role in anterior cruciate ligament and posterior cruciate ligament injury. The possible differences among age, sex, and ethnicity in PTS have not yet been reported. Purpose: To describe demographic variances of proximal tibial anatomy and to detect differences in regard to ethnicity, sex, and age. Study Design: Cross-sectional study; Level of evidence, 3. Methods: In total, 250 cadaveric specimens with full-body c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…This condition may show that preoperative evaluation should be made separately for each knee of patients before orthopedic surgeries and the slope for high tibial osteotomies might be different for left and right knees in the same patient. According to our evaluations, MPTS, LPTS, and GPTS means were almost similar for both genders as seen in Figure 5 , which was parallel to the findings of Kumar et al [ 24 ] and Clinger et al [ 25 ] On the other hand, contradictory findings such as lower LPTS values for females have been presented previously by Meier et.al. [ 13 ] Like the study performed by Clinger et al, [ 25 ] in our study, age did not present any significant difference in terms of MPTS, LPTS, and GPTS values.…”
Section: Discussionsupporting
confidence: 91%
“…This condition may show that preoperative evaluation should be made separately for each knee of patients before orthopedic surgeries and the slope for high tibial osteotomies might be different for left and right knees in the same patient. According to our evaluations, MPTS, LPTS, and GPTS means were almost similar for both genders as seen in Figure 5 , which was parallel to the findings of Kumar et al [ 24 ] and Clinger et al [ 25 ] On the other hand, contradictory findings such as lower LPTS values for females have been presented previously by Meier et.al. [ 13 ] Like the study performed by Clinger et al, [ 25 ] in our study, age did not present any significant difference in terms of MPTS, LPTS, and GPTS values.…”
Section: Discussionsupporting
confidence: 91%
“…It is suspected that the relatively small sample size and inability to match by age and sex in this study limited further evaluation of the role of skeletal maturity and TEF. Interestingly, in a study using computed tomography to measure PTS, Clinger et al 7 found no difference in PTS among sex or age groups. However, the study excluded individuals <18 years old and utilized a different imaging modality and measurement method than that used in our study and the majority of studies concerning PTS, perhaps attributing to these unique findings.…”
Section: Discussionmentioning
confidence: 98%
“…A recent cadaveric study using 3-dimensional computed tomography reported that the mean PTS was 8.92°(range, -9.4°to 14.95°) and that nearly 25% of specimens had clinically significant slopes of \6°or .12°. 5 The broadspectrum PTS is known to have a significant effect on in situ forces together with the cruciate ligaments, altering the kinematics of the knee joint by anteriorly or posteriorly shifting the resting position of the tibia. 6,8,22 Although the relationship between the PTS and ACL injuries or graft failure has been actively studied in various groups, 15,17,21,31 little attention has been paid to the relationship between the PTS and PCL injuries or graft failure.…”
Section: Discussionmentioning
confidence: 99%
“…A recent cadaveric study using 3-dimensional computed tomography reported that the mean PTS was 8.92° (range, –9.4° to 14.95°) and that nearly 25% of specimens had clinically significant slopes of <6° or >12°. 5 The broad-spectrum PTS is known to have a significant effect on in situ forces together with the cruciate ligaments, altering the kinematics of the knee joint by anteriorly or posteriorly shifting the resting position of the tibia. 6,8,22…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation